2010
DOI: 10.7127/rbai.v4n300011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação qualitativa das águas subterrâneas para irrigação na região do baixo jaguaribe – ceará

Abstract: , carbonates (CO-3), Bicarbonate (HCO-3), sulphate (SO 4-2) and electrical conductivity (CEa). We used the software Qualigraf to classify the samples by the Piper diagram. The results showed that 87.5% of ions cations were dominated water with sodium and 47.5% of anions fit water bicarbonate, and chloride, but according to the overall predominant water with sodium bicarbonate 47.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
4
1
1
Order By: Relevance
“…Probably, the higher sodium contents are due to higher water withdrawals from these underground wells, associated to the low rainfall period, as a consequence the salts become more concentrated, indicating that they need to be cautious about the use of this water for irrigation, choosing crops adapted to these conditions. In the municipality of Limoeiro do Norte, Ceará states, Barroso et al (2010) found lower Na + values than in this study 9.03 and 8.03 mmol c L -1 , in the months of July and August, respectively. In the Chapada do Apodi-CE, Fernandes et al (2005) found Na + values ranged 65.4-160.6 mg L -1 , corresponding to 2.84 to 6.98 mmol c L -1 .…”
Section: Sar Hardness Cations Anionscontrasting
confidence: 84%
See 1 more Smart Citation
“…Probably, the higher sodium contents are due to higher water withdrawals from these underground wells, associated to the low rainfall period, as a consequence the salts become more concentrated, indicating that they need to be cautious about the use of this water for irrigation, choosing crops adapted to these conditions. In the municipality of Limoeiro do Norte, Ceará states, Barroso et al (2010) found lower Na + values than in this study 9.03 and 8.03 mmol c L -1 , in the months of July and August, respectively. In the Chapada do Apodi-CE, Fernandes et al (2005) found Na + values ranged 65.4-160.6 mg L -1 , corresponding to 2.84 to 6.98 mmol c L -1 .…”
Section: Sar Hardness Cations Anionscontrasting
confidence: 84%
“…There are no severe restrictions on carbonate or bicarbonate content for irrigation (Nakayama & Bucks, 1986). Barroso et al (2010) found lower values for bicarbonate in groundwater in Limoeiro do Norte-CE (1.72 to 1.95 mmol c L -1 ). For sulphate (SO 4 2-) the lowest value was in well 6 (0.59 mmo c L -1 ).…”
Section: Sar Hardness Cations Anionsmentioning
confidence: 71%
“…Uma característica inerente aos métodos de irrigação localizados é a pequena área de passagem da água nos emissores. Em função dos pequenos diâmetros de orifício, o entupimento dos emissores configura-se como um dos principais problemas relacionados ao método (GILBERT; FORD, 1986) Segundo Ribeiro et al (2004) que para o bom desempenho de um sistema de irrigação é necessário levar em consideração fatores como qualidade da água e presença de partículas inorgânicas e orgânicas além dos relativos ao funcionamento mecânico do sistema De acordo com Barroso et al (2010), para o estudo da qualidade da água para fins de irrigação, dá se destaque à composição química da água, embora as características físicas e a carga de sedimentos devem ser consideradas importantes. Na irrigação localizada, um dos fatores que eleva os custos de operação e manutenção do sistema e, em certos casos, inviabiliza a utilização desse método é a obstrução dos emissores (PATERNIANI; SCATOLINI, 2001).…”
Section: Introductionunclassified
“…The TDS and EC in streams are usually higher during low flow periods than during high flow periods. The semiarid zone is characterized as a region of high temperatures and high temporal and spatial rainfall variability; therefore, water shortage is the major limiting factor in agricultural production (BARROSO et al, 2010). …”
Section: Hydrochemistry Assessmentmentioning
confidence: 99%
“…The samples were collected both at the end of the dry periods (December 2009 and2010) and during rainy days (August 2009 and 2010) of each hydrologic period, thus totaling four sampling times. Some dams dried up at the end of the 2010 rainy season and so it was not possible to sample all points.…”
Section: Area and Collection Of Samplesmentioning
confidence: 99%